The TSPO-NOX1 axis controls phagocyte-triggered pathological angiogenesis in the eye - Wolf, Anne (Nat Commun, 2020)
Aberrant immune responses including reactive phagocytes are implicated in the etiology of age-related macular degeneration (AMD), a major cause of blindness in the elderly. The translocator protein (18 kDa) (TSPO) is described as a biomarker for reactive gliosis, but its biological functions in retinal diseases remain elusive. Here, we report that tamoxifen-induced conditional deletion of TSPO in resident microglia using Cx3cr1(CreERT2):TSPO(fl/fl) mice or targeting the protein with the synthetic ligand XBD173 prevents reactivity of phagocytes in the laser-induced mouse model of neovascular AMD. Concomitantly, the subsequent neoangiogenesis and vascular leakage are prevented by TSPO knockout or XBD173 treatment. Using different NADPH oxidase-deficient mice, we show that TSPO is a key regulator of NOX1-dependent neurotoxic ROS production in the retina. These data define a distinct role for TSPO in retinal phagocyte reactivity and highlight the protein as a drug target for immunomodulatory and antioxidant therapies for AMD.